Pengaruh Aktivasi Fisik Zeolit Alam sebagai Adsorben dalam Proses Adsorpsi Minyak Jelantah - Paramita Dewi Sukmawati (Poltekkes Kemenkes Yogyakarta, 2017)
Used cooking oil when consumed will cause some diseases to humans. However, if it is discharged into the environment, it will pollute the surrounding environment. In order that the usedcooking oil can be reused, purification process is needed by means of adsorption technique. Oneof the factors that influencing the effectiveness of adsorption is the surface area of an adsorbent.To do so, adsorbent activation is needed to be applied, as well. This research was aimed to findcondition of optimum temperature and time in the activation process of natural zeolite physically.The physical activation process of natural zeolite includes grinding natural zeolite using porcelainmill and sifting it, so that it is similar in size to 100 mesh. And then heating it in a furnace with avariable heating temperature of ± 200, 300, 400, 500 and 600 °C, meanwhile the variable ofheating time was set to 90, 135, 180, 225 and 270 minutes and then cooling it in the desiccator.After that, the adsorption test on used cooking oil was held using the activated natural zeolite toknow the condition of optimal heating activation of temperature and time. The optimum conditions obtained in this study was ± 400 °C for the heating temperature and 225 minutes for theheating time with a numeric value of free fatty acids amounting to 0,8138 % and saponificationvalue of the number amounting to 180.589 mg KOH/g.